2002
DOI: 10.1103/physrevb.66.174429
|View full text |Cite
|
Sign up to set email alerts
|

Slater-Pauling behavior and origin of the half-metallicity of the full-Heusler alloys

Abstract: Using the full-potential screened Korringa-Kohn-Rostoker method we study the full-Heusler alloys based on Co, Fe, Rh and Ru. We show that many of these compounds show a half-metallic behavior, however in contrast to the half-Heusler alloys the energy gap in the minority band is extremely small due to states localized only at the Co (Fe, Rh or Ru) sites which are not present in the half-Heusler compounds. The full-Heusler alloys show a Slater-Pauling behavior and the total spin-magnetic moment per unit cell (Mt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

55
521
2
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,823 publications
(586 citation statements)
references
References 68 publications
(60 reference statements)
55
521
2
8
Order By: Relevance
“…Since the half-Heusler alloy NiMnSb was firstly predicted to be a half-metallic ferromagnet (HFM) by utilizing the first principles calculations in 1983 [1], new half-metallic Heusler alloys, which are metallic for one spin direction while semiconducting for the other spin direction, have always received the theoretical and experimental attention due to their potential applications in the fields of magnetic sensors, tunnel junctions and other spintronic devices [2][3][4]. Heusler alloys, with structural formulas of X 2 YZ (with L2 1 structure) and XYZ (with Cl b structure), in which X and Y are transition * E-mail: rahmounemohammed@yahoo.fr metals and Z is a main-group element, are one of the most attractive HM materials, since they can be synthesized easily and their Curie temperatures are high [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the half-Heusler alloy NiMnSb was firstly predicted to be a half-metallic ferromagnet (HFM) by utilizing the first principles calculations in 1983 [1], new half-metallic Heusler alloys, which are metallic for one spin direction while semiconducting for the other spin direction, have always received the theoretical and experimental attention due to their potential applications in the fields of magnetic sensors, tunnel junctions and other spintronic devices [2][3][4]. Heusler alloys, with structural formulas of X 2 YZ (with L2 1 structure) and XYZ (with Cl b structure), in which X and Y are transition * E-mail: rahmounemohammed@yahoo.fr metals and Z is a main-group element, are one of the most attractive HM materials, since they can be synthesized easily and their Curie temperatures are high [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the half-metallic ferromagnetic nature theoretically predicted for some of these alloys [10], [11] and because of their high Curie temperatures, which are well above room temperature (RT) [12]. We recently reported fully epitaxial magnetic tunnel junctions (MTJs) with a Co-based full-Heusler alloy thin film of either Co Cr Fe Al (CCFA) or Co MnGe as a lower electrode and a MgO tunnel barrier and obtained relatively high tunnel magnetoresistance (TMR) ratios at RT for these epitaxial MTJs (e.g., 42% for CCFA-MTJs at RT) [3], [6], [8].…”
mentioning
confidence: 99%
“…In addition, one spin band (majority spin) of HMHA exhibits metallic behavior, while the other spin band (minority spin) displays semiconductor behavior, and such a band structure could generate a high spin polarized current. Therefore, HMHA has been explored as an electrode of CPP-SV to achieve a high magnetoresistance (MR) ratio [5][6][7][8][9][10][11]. Takayashi et al reported a large MR ratio of 74.8% at room temperature (RT) in CPP-SV using Co 2 MnGa 0.…”
Section: Introductionmentioning
confidence: 99%